The Implementation of Snowball Throwing Strategy in Teaching Reading Narrative Text Class X of MA Miftahul Ulum Bettet Pamekasan - Khoirot, Fatwatul; YB, Dinar Vincy (DIDAKTIKA, 2023)
This research was conducted to determine the application of snowball throwing method which is used to determine the reading ability of class X IPS F MA Miftahul Ulum Bettet Pamekasan in reading English sentences. To analyse the data, the researchers used method of throwing snowballs. The design of this study is descriptive qualitative. The Researchers used three techniques in collecting data, namely observation, interviews and questionnaires. The results of the implementation show that snowball throwing made the students became very enthusiastic in carrying out the snowball throwing strategy. Further, the results of the problems faced by students in reading narrative texts were phonics problems of 8 students, fluency problems of 10 students, vocabulary problems of 5 students, and finally competence problems of 10 students. While the results of internal and external factors that affect students' ability to read narrative texts are that 33 students experience internal and external factors in reading narrative texts.